Prevalence of temporomandibular disorders and its association with parafunctional habits among senior-secondary school children of Lucknow, India - Kriti Agarwal; Sabyasachi Saha; Pooja Sinha (Wolters Kluwer Medknow Publications, 2016)
Introduction: Temporomandibular disorders (TMD) are defined as heterogeneous group of psychological disorders, commonly characterized by orofacial pain, chewing dysfunction, or both. Aim: To determine the prevalence of TMD and to describe the association between parafunctional habits and signs and symptoms of TMD among 15-17-year-old school children in Lucknow. Materials and Methods: This study followed a cross-sectional design, with a sample of 407 school children aged 15-17-year-old. A single, trained, calibrated investigator interviewed the participants according to Fonseca's Anamnestic Questionnaire-1994, which provided information on the prevalence of TMD, followed by the clinical examination of temporomandibular joint (TMJ) according to WHO (1997). Chi-square test and Univariate and Multivariate Logistic Regression analysis were used. Results: The prevalence of TMD was (22.4%). There was no statistically significant association was found between age, (P = 0.81) gender (P = 0.09) and TMD. Nail-biting (88.3%) was the most common habit, followed by clenching/grinding (68.4%) and mouth breathing (53.4%). However, habits and TMJ symptoms were found statistically significant P < 0.01 or P < 0.001 associated to TMD. Further, adjusted (age and gender) logistic regression analysis revealed that digit-sucking, mouth breathing, nail biting, and clenching has made a significant contribution to prediction (P < 0.001). Conclusion: The habits especially digit-sucking, mouth breathing, nail biting, and clenching had statistically significantly associated with TMD.